Defining criterias of shariah compliant hotel rooms - Saifuddin, Syaza; Othman, Rashidi; Md Hashim, Muhammad Hafizuddin Akmal; Jasmani, Ismail; Abdul Majid, Noor Hanita (American Scientific Publishers, 2017)
This paper defines criteria of various sampling locations used to test out the criteria of what a Fully Shariah Compliant Hotel Room should be. This paper reviews the theoretical views in establishing a suitable and optimum environment for Muslim in a supposedly fully shariah-compliant environment. It involves a few research methodologies that require the researcher to study on a few characteristics needed to test out whether the proper criteria are applied to ensure that the awarded fully shariah-compliant hotel rooms comply to the needs of Muslim guests. This paper intends on revealing the elements that are vital and may contribute for hotels in achieving a more conclusive research on space planning for hotel rooms focusing on the shariah and Muslim guests.